Two new halogenated metabolites from the red alga Laurencia sp. Issue 1 (2nd January 2023) - Wang, Zhao-Cong; Wang, Yan; Huang, Li-Ying; Liao, Xiao-Jian; Jiang, Zhi-Hui; Xu, Shi-Hai; Zhao, Bing-Xin
Abstract: Two new halogenated metabolites, laurenhalogens A (1 ) and B (2 ), along with four known ones (3–6 ), were isolated from the red alga Laurencia sp. The structures of 1 and 2 were determined by the means of UV, IR, MS, NMR and X-ray diffraction analysis. In addition, the antibacterial activities of 1 –6 were also evaluated. Graphical Abstract: UF0001